Address before the Economic and Social Council of the United Nations - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, spoke about the fifth annual report and a supplemental statement to show what Bank was doing to enlarge the freedom of men. He described the Bank functioning effectively as a pool of both the government and private resources. He spoke about the bonds of International Bank that are well established in the America securities market. He warned of inflation risks and equipment shortages due to the Korean War. He spoke of the need for international coordination of the many sources of financing and aid.